The Transformation of Aqidah Akhlak Values in Shaping Taqwa Character and Scientific Discipline among Santri: An Ethnographic Study at Putri Salafiyah Bangil and Banat 2 Sidogiri Islamic Boarding Schools - Aviah Asma’ul Husna; Chusnul Muali; Mona Novita; Abdur Rahman Nor Afif Hamid (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study examines the transformation of Aqidah Akhlak values in shaping the character of taqwa (God-consciousness) and the attitude of scientific discipline among female students (santri) at Pondok Pesantren Putri Salafiyah Bangil and Banat 2 Sidogiri. The research employed a qualitative approach with an ethnographic design. Data were collected through participant observation, in-depth interviews, and documentation, involving the pengasuh (caregivers), ustazah (female teachers), administrators, senior students, and active students. The findings reveal that the transformation of values occurs through instruction, role modeling, habituation, supervision, the application of ta‘zīr (educational sanctions), and the involvement of students in organizational management and teaching activities. This process develops from rule-dependent obedience toward the formation of habits and personal awareness. The character of taqwa is reflected in the regular performance of worship, honesty, self-control, fulfillment of responsibilities, and concern for others. Meanwhile, the attitude of scientific discipline is demonstrated through diligence in attending religious lessons, reading and reviewing classical Islamic texts (kitab), maintaining proper etiquette toward teachers, managing time effectively, preparing lessons, and completing assignments without continuous reminders. This study identifies two models of value transformation. Salafiyah Bangil exhibits a relational-collective model based on the close interaction among administrators, amidi (student coordinators), senior students, and dormitory supervisors. In contrast, Banat 2 Sidogiri demonstrates a charismatic-structural model strengthened by the exemplary leadership of Bu Nyai, collective activities, and the consistent enforcement of institutional regulations. Both models indicate that the success of pesantren education is not merely reflected in students’ compliance with rules, but also in the development of religious awareness, responsibility in learning, and readiness to guide and mentor other students.